A Case Study of Public Private Partnership in the Construction Sector in Ho Chi Minh City, Vietnam - Doan, Vu Vi (2021)
Public Private Partnership PPPs in developed countries exhibit a successful strategy along with the framework that while appealing the private sector, the role for state in ensuring that social responsibilities have been met and successful sector reforms and public investment achieved. PPPs depicts a number of recognized benefits for the public sector to exploit especially in terms of benefiting the public infrastructure. This also caters the aptitude to promote the additional finance in an environment of budgetary restrictions, also ensure the effective use of private sector operational efficiencies for reducing the cost and further to increase the quality of services provided to the public and the ability to speed up infrastructure development. The purposes of this study are to assess the existing conditions that are enabling and disenabling the applying of PPP arrangement infrastructure in Ho Chi Minh city with focusing on legal, regulatory, and policy framework, institutional framework, technical issues, investment and socioeconomic issues, stakeholders consultation, financing requirements, risk management and managing the interface between public and private partners, to identify key factors for influencing successful Public-Private Partnerships in infrastructure projects and the constraints and up to now the features of a good relationship management of PPP projects. The findings show the lack of readiness of infrastructure sector for implementing large-scale PPP projects and the study recommended according to analysis that the state should take actions for enabling a successful PPP in infrastructure and mitigating the gap which is required for PPP project’s development and implementation. The important steps are establishing a sound of legal and institutional framework, develop policies and guidelines, creating a stable environment and conducive to investment with the aim of encouraging private sector investments in the water and wastewater sector, developing a strategic framework for relationship management of PPP projects to enable both public and private sectors to manage these important PPP relationships successfully. There was the total of 150 questionnaires were sent out, and the total of 400 valid answer was obtained for data analysis tool. As major successful ingredients to be indicated to the most crucial factor for evaluating the public and private sectors. Moreover, the effectiveness related to the cost and also the financial attraction have been taken as highly recognised evaluation factors which could ranked by the public sector and private consortium respectively. In addition, the “existence of a long-term demand for the proposed services”, further availability of “strong private consortium”, alignment with state’s “strategic objectives”, as well as reliable “service delivery” need to be rated as highly important to the success of PPP schemes. On the other side, the tripartite expectations need to be ensured as indispensable for making the feasibility and successful delivery of public services and infrastructure projects via PPP scheme in Ho Chi Minh City in infrastructure projects. This study enables international and domestic construction companies to better understand how success and constraints should be assessed and allocated for PPP project in Ho Chi Minh City in infrastructure. It also assists in constraints and success response planning and control for future PPP projects in Ho Chi Minh City in infrastructure projects.